VIRTUAL FASHION DESIGN STUDIO: AI-DRIVEN CO-CREATION PLATFORM FOR DESIGNERS AND MACHINES - Mani Nandini Sharma; Sahu, Damini; Singh, Vashisht; Mulla, Rafat Aslam; Ali, Dr. Syed Sumera; Kumar, Jambi Ratna Raja (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Artificial intelligence is developing very quickly, and this has had a big impact on artistic fields like fashion design. This study presents a new Virtual Fashion Design Studio that is powered by AI and makes it easier for human creators and smart systems to work together to make things. The suggested platform combines cutting-edge generated models with engaging user interfaces. This will let fashion designers work together with machines to come up with ideas, improve them, and see how they'll look. The system lets users enter text or pictures, which are then read and built upon by AI to come up with different design ideas. It does this by using natural language processing, image generation, and ranking algorithms. The platform allows for iterative improvement by having feedback loops where users can rate or change designs that have been created. This creates a dynamic relationship between human insight and machine creation. The system also understands the context by looking at things like colour theory, fashion trends, fabric patterns, and how well styles match. This makes sure that the results are useful and practical. The goal of this joint framework is to make fashion design more accessible by giving both new and experienced designers smart tools that boost inspiration and productivity. Usability studies show that the platform cuts creation time by a large amount while also making users happier and coming up with more ideas. These findings show that AI could be useful in fashion design, but not as a replacement. Instead, it could be a creative partner who helps humans do their best work. This work adds to the growing conversation about how humans and AI can work together in the arts. It imagines a world where designers and intelligent systems can work together to speed up design innovation.